Selective lanthanide sorption and mechanism using novel hybrid Lewis base (N-methyl-N-phenyl-1,10-phenanthroline-2-carboxamide) ligand modified adsorbent - Awual, Md. Rabiul; Kobayashi, Tohru; Miyazaki, Yuji; Motokawa, Ryuhei; Shiwaku, Hideaki; Suzuki, Shinichi; Okamoto, Yoshihiro; Yaita, Tsuyoshi (Journal of hazardous materials, 2013)
•Hybrid Lewis base adsorbent was prepared for selective lanthanide (Eu, Sm) removal.•Common ions did not interfere due to strong interactions between Eu/Sm and adsorbent.•The adsorbent has good sorption and kinetic performances for potential applications.•The adsorption is reversible and adsorbent reusable in many cycles without any deterioration. This study aims to develop a highly selective Lewis base adsorbent to investigate the selective sorption and recovery of Eu(III) and Sm(III) from wastewater. The oxygen and nitrogen donor atoms containing Lewis base N-methyl-N-phenyl-1,10-phenanthroline-2-carboxamide (MePhPTA) ligand was synthesized and subsequently an adsorbent was prepared by direct immobilization onto mesoporous silica. Determined maximum adsorption capacities were 125.63 and 124.38mg/g for Eu(III) and Sm(III), respectively. Experiments with mixed-cations solutions showed that the sequence of preferential adsorption was Eu(III)>Sm(III). The lanthanide sorption by hybrid Lewis base adsorbent (HyLBA) was not adversely affected by the presence of sodium, potassium, calcium, magnesium, chloride, sulfate and nitrate ions due to strong affinity between hard Lewis acid lanthanide and hard Lewis base adsorbent. The crystallography for the Sm-MePhPTA complex suggested that MePhPTA was strongly coordinated to Sm(III) with oxygen and nitrogen by forming a stable complex with two 5-membered rings. The data clarified that bond lengths between Sm(III) and amide oxygen (2.475Å) were shorter than SmN (2.662Å) in phenanthroline moiety indicating strong oxygen driven HyLBA. The results suggested that HyLBA has a good prospect of promising applications for separation/sorption of lanthanide ions from effluents.